Strategi Akselerasi Insurtech Syariah Dalam Meningkatkan Partisipasi Asuransi di Indonesia: (Studi Kasus Sinarmas Insurtech) - Lubis, Fatimah Aini; Nurbaiti, Nurbaiti; Nurwani, Nurwani (Jayapangus Press, 2025)
There is considerable room for expansion in Indonesia’s Islamic financial sector, including Islamic insurance. However, awareness and participation in Islamic insurance remain low. Using Sinarmas Insurtech as a case study, this research seeks to identify strategies for accelerating InsurTech adoption to increase the number of Islamic insurance clients in Indonesia. The methodology used was qualitative research with a phenomenological approach. Semi-structured interviews, documentation, and a literature review were used to collect data. The findings indicate that Sinarmas Insurtech’s implementation of InsurTech technology has improved Islamic insurance literacy and inclusion in Indonesia. Through innovative app-based services, digital marketing, and end-to-end e-channel processes, the company has successfully provided convenience and comfort to customers. Educational programs, collaborations with Islamic financial institutions, and the provision of affordable insurance products have also played a significant role in expanding the reach of the Islamic insurance market.